Element by element prediction model of condensation heat transfer on a horizontal integral finned tube - Al-Badri, Alaa; Gebauer, Thomas; Leipertz, Alfred; Fröba, Andreas Paul (International Journal of Heat and Mass Transfer, 2013)
The paper presents an analytical model to calculate the condensation heat transfer coefficient on an integral finned tube. The model depends on elemental calculations by dividing the tube wall into small annular elements. It takes into consideration the local temperature distribution on the outside surface of the finned tube, the local heat transfer rate and the height of condensate in the channel between fins. The model is able to predict the heat transfer for different fin profiles. Gravity force and surface tension forces are included in the model, where for the latter a linear pressure distribution over the fin is assumed. For the verification of the present model, experimental data for a copper standard finned tube with 1, 1, 1, 2-tetrafluoroethane (R134a) and propane (R290) from our experimental work were used. Within this work, experiments were performed for a steel standard finned tube with R290. For tubes having more than 40 fins per inch (FPI), it could be shown that the channel between fins can be approximated to be trapezoidal or rectangular. This approximation is also applicable for the condensation on tubes having 26 FPI or larger if the subcooling between the saturated vapour and the tube wall is larger than a certain value depending on the working fluid. In comparison to previous analytical models, the present model agrees well with the experimental data and predicts these data with a mean absolute percentage deviation of 4.7%. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Analytical model; Condensation; Finned tube; Heat transfer coefficient; Temperature distribution